1997
DOI: 10.1063/1.474864
|View full text |Cite
|
Sign up to set email alerts
|

Exchange and correlation energy in density functional theory: Comparison of accurate density functional theory quantities with traditional Hartree–Fock based ones and generalized gradient approximations for the molecules Li2, N2, F2

Abstract: The density functional definition of exchange and correlation differs from the traditional one. In order to calculate the density functional theory ͑DFT͒, quantities accurately, molecular Kohn-Sham ͑KS͒ solutions have been obtained from ab initio wave functions for the homonuclear diatomic molecules Li 2 , N 2 , F 2 . These afford the construction of the KS determinant ⌿ s and the calculation of its total electronic energy E KS and the kinetic, nuclear-attraction and Coulomb repulsion components T s , V, W H a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 48 publications
5
116
0
1
Order By: Relevance
“…Within the density functional framework, Baerends et al indicated that the single-determinant wave function includes all the electron correlation contributions to the energy, even the nondynamic correlation. 35 In DFT calculations the energy of the singlet state can be approximated in principle using that of the single-determinant BS state 1 , BS which was confirmed by the good results obtained by Perdew et al 36 for the atomization energy of H with such approximation to the energy of the 2 singlet. These authors indicated that such a BS state describes the electron density and the on-top electron pair density with remarkable accuracy, even if it gives an unrealistic distribution of the spin density, and propose that the BS single-determinant wave function is the correct solution for the Kohn᎐Sham equations.…”
Section: Evaluation Of Coupling Constant From Dft Calculationsmentioning
confidence: 56%
“…Within the density functional framework, Baerends et al indicated that the single-determinant wave function includes all the electron correlation contributions to the energy, even the nondynamic correlation. 35 In DFT calculations the energy of the singlet state can be approximated in principle using that of the single-determinant BS state 1 , BS which was confirmed by the good results obtained by Perdew et al 36 for the atomization energy of H with such approximation to the energy of the 2 singlet. These authors indicated that such a BS state describes the electron density and the on-top electron pair density with remarkable accuracy, even if it gives an unrealistic distribution of the spin density, and propose that the BS single-determinant wave function is the correct solution for the Kohn᎐Sham equations.…”
Section: Evaluation Of Coupling Constant From Dft Calculationsmentioning
confidence: 56%
“…Approximate correlation energies of H 2 as a function of bond length are available from Ref. [30]. From these data we find that for H 2 at the equilibrium bond length λ(R e = 1.401a.u.)…”
Section: Moleculesmentioning
confidence: 96%
“…Time-dependent DF theory, based on the theorem of Runge and Gross (1984), has proved to be valuable in predicting the excited states and optical properties in molecules (Burke, Werschnik, and Gross, 2005;Marques et al, 2006;Botti et al, 2007;Isegawa, Peverati, and Truhlar, 2012) and has become an option in most DF program packages. In addition, the exact KS potential can be determined if the exact wave functions are known, and Gritsenko, Schipper, and Baerends (1997) showed that eigenvalue differences provide an excellent approximation to excitation energies in several small molecules when calculated with this potential.…”
Section: Excitations and Eigenvaluesmentioning
confidence: 99%